Hypocretin (orexin) regulation of sleep-to-wake transitions - De Lecea, Luis; Huerta, Ramon (Frontiers in Pharmacology, 2014)
The hypocretin (Hcrt), also known as orexin, peptides are essential for arousal stability. Here we discuss background information about the interaction of Hcrt with other neuromodulators, including norepinephrine and acetylcholine probed with optogenetics. We conclude that Hcrt neurons integrate metabolic, circadian and limbic inputs and convey this information to a network of neuromodulators, each of which has a different role on the dynamic of sleep-to-wake transitions. This model may prove useful to predict the effects of orexin receptor antagonists in sleep disorders and other conditions.